The World through the Eyes of Travel Writers: Agustinus Wibowo’s Selimut Debu and Jihan Davincka’s Memoar of Jeddah - Shofi Mahmudah Budi Utami; Muammar Kadafi; Ambhita Dhyaningrum; Muhammad Hary Rusli (Jurnal Lingua Idea, 2022)
This paper investigates depictions of the world in two travel stories by Agustinus Wibowo in Selimut Debu (2010) and Jihan Davincka in Memoar of Jeddah (2013). The dissimilarity of both stories particularly in projecting the view of the world does not only accentuate different nuances but also the propensity of authors’ observations towards the objects they encounter such as places, people, and culture. Therefore, this study focuses on how travel writings own distinct ways in narrating the story of the author’s journey. In accordance with the problem, this study employed theoretical concepts proposed by Thompson specifically about reporting the world; that travel writers have certain tendency in their descriptions of the objects they see and involvement of the ‘self’ during the journey. This study then explores these two works to seek the data indicating the subjectivity to be sequentially selected and analysed. Eventually, it is found that Selimut Debu performs alteration in the involvement of the ‘self’; while Memoar of Jeddah emphasises more on personal involvement.